IMPLEMENTATION OF GREEN OPEN SPACE PROGRAM: CASE STUDY IN CIRUAS CITY PARK, SERANG REGENCY - Leniken, Diska; Arazi, Shabilah; Juliani, Nurul Hikmah; Pratama, Diva Putra; Gulo, Edison Kurniawan (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
One important component of a city is green open space, which serves to balance the ecological conditions of an area so that the development of modern development can be balanced with the ecosystem. The Ciruas City Park Green Open Space Program in Serang Regency is needed because several sub-districts in Serang Regency are industrial areas, which cause a lot of air pollution and the need for greening. This research method uses a qualitative approach and a literature review approach. In this study, the theory used, the policy implementation model proposed by G. Shabbir Cheema and Dennis A. Rondinelli, includes four factors: environmental conditions, inter-organizational relationships, resources, and the characteristics and abilities of implementing agents. The objectives to be achieved in this study are: (i) To find out how the implementation of the Ciruas City Park Green Open Space Program in Serang Regency is carried out, and (ii) What factors influence the implementation of the Ciruas City Park Green Open Space Planning Program in Serang Regency. Based on the studies that have been conducted, the research concludes that the Ciruas City Park Green Open Space Program in Serang Regency has not been maximized. This is due to many influencing factors such as the bad habits of the community and the lack of government attention to facilities.